2022
DOI: 10.15388/amed.2022.29.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Dopamine Agonists in the Treatment of Prolactinomas

Abstract: The article is devoted to the conservative treatment of hyperprolactinemia of tumor origin. Cabergoline is considered as an effective treatment not only for microadenomas but also for large pituitary tumors which is illustrated by the clinical case of the patient P. The most important effects of cabergoline demonstrated in this clinical case are reduction in the size of the adenoma from macro to micro, reverse development of chiasmal syndrome with restoration of visual functions, achievement and maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…So, the ambiguity of the identified risk factors for the development of resistance to DAs is confirmed by the data of other authors and our own observations [ 20 ]. Based on a retrospective assessment of the treatment outcomes in patients with prolactinomas, Araujo-Castro M. et al argue that large tumor size, but not male gender, is a risk factor for DAs resistance [ 21 ].…”
Section: Dopamine Agonist Resistancesupporting
confidence: 86%
See 1 more Smart Citation
“…So, the ambiguity of the identified risk factors for the development of resistance to DAs is confirmed by the data of other authors and our own observations [ 20 ]. Based on a retrospective assessment of the treatment outcomes in patients with prolactinomas, Araujo-Castro M. et al argue that large tumor size, but not male gender, is a risk factor for DAs resistance [ 21 ].…”
Section: Dopamine Agonist Resistancesupporting
confidence: 86%
“…Our own experience indicates a pronounced therapeutic efficacy in the treatment of macroprolactinoma complicated by compression syndrome in men with average therapeutic doses of cabergoline. At the same time, we observed a young woman with microprolactinoma and the initial absence of any response to the use of DAs, despite an increase in the dose of the drug [ 20 ]. Szmygin H. et al also observed a 26-year-old woman with microadenoma, whose treatment was complicated by both primary resistance to all drugs of the DAs group, and their poor tolerance [ 12 ].…”
Section: Dopamine Agonist Resistancementioning
confidence: 99%